2017
DOI: 10.1128/aac.01992-16
|View full text |Cite
|
Sign up to set email alerts
|

N -Acetyl- l -Cysteine and Cysteamine as New Strategies against Mixed Biofilms of Nonencapsulated Streptococcus pneumoniae and Nontypeable Haemophilus influenzae

Abstract: Acute otitis media, a polymicrobial disease of the middle ear cavity of children, is a significant public health problem worldwide. It is most frequently caused by encapsulated Streptococcus pneumoniae and nontypeable Haemophilus influenzae, although the widespread use of pneumococcal conjugate vaccines is apparently producing an increase in the carriage of nonencapsulated S. pneumoniae. Frequently, pneumococci and H. influenzae live together in the human nasopharynx, forming a self-produced biofilm. Biofilms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 63 publications
6
26
0
1
Order By: Relevance
“…In fact, S. pneumoniae and NTHi are the predominant othopathogens associated with otitis media as identified through bacterial culture [10] and frequently form mixed biofilms. Taking advantage of the in vitro mixed NTPn-NTHi biofilm development procedure recently developed [27], we tested the antimicrobial effect of EBA 31 and showed that this compound also demonstrated inhibiting and disintegrating properties in this system (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, S. pneumoniae and NTHi are the predominant othopathogens associated with otitis media as identified through bacterial culture [10] and frequently form mixed biofilms. Taking advantage of the in vitro mixed NTPn-NTHi biofilm development procedure recently developed [27], we tested the antimicrobial effect of EBA 31 and showed that this compound also demonstrated inhibiting and disintegrating properties in this system (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial strains used for mixed biofilms were NTHi 54997 and the novobiocin-resistant (Nov r ) NTPn P233 (Table 2). Biofilm formation was assessed with crystal violet [27]. NTHi 54997 was grown at 37C in sBHI medium as described above to an OD550 of 0.5, sedimented by centrifugation, resuspended in an equal volume of C+Y (individual scans at 0.5 µm intervals) and x-z (images at 6 µm intervals) planes.…”
Section: Mixed Biofilm Formation Assay and Quantification Susceptibimentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA‐approved N ‐acetyl cysteine (NAC), whose mucolytic ability to dissociate disulfide bonds in extracellular mucin proteins and reduce their viscosity, was subsequently expounded into a potential anti‐biofilm agent. NAC was employed in modern applications, such as combinatorial treatment with cysteamine, an antioxidant against mixed biofilms of Streptococcus pneumoniae and Haemophilus influenzae . Another garlic‐derived compound, raffinose, could inhibit biofilms by binding to lectin‐A, which is an exopolysaccharide‐binding protein in P. aeruginosa …”
Section: Development Of Anti‐biofilm Chemotherapymentioning
confidence: 99%
“…Haemophilus influenzae is the second most common causative bacterium of community-acquired pneumonia, following Streptococcus pneumoniae , and has taken the leading position after pneumococcal vaccines became popular (1). β-Lactam antibiotics have previously been used for the treatment of community-acquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%